Adjunctive Soft-Skills Training Combined with Group-Based Psychosocial Support for Future Web Developers Screening Positive for Post-Traumatic Stress Symptoms During Wartime: A Three-Arm Quasi-Experimental Study - Nina Pidbutska; Anastasiia Knysh; Yuliia Chebakova; Yuliia Demidova (Physical Rehabilitation and Recreational Health Technologies, 2026)
Purpose. Ukrainian web-development students face prolonged wartime stressors, yet psychosocial support tailored to this group remains scarce. We examined whether adding brief soft-skills training to group-based psychosocial support produced greater reductions in self-reported post-traumatic stress symptoms than support alone in students screening positive for probable PTSD. Materials & Methods. In a three-arm quasi-experimental study with random allocation (March–September 2024), 181 students scoring ≥33 on the PCL-5 (used as a screening instrument, not for clinical diagnosis) were allocated to monitoring only (Arm A, n=60), twelve weekly online psychosocial support sessions (Arm B, n=59), or support plus four soft-skills modules (Arm C, n=62). The primary outcome was PCL-5 total score change. Results. Of 181 randomised participants, 170 (93.9%) completed both assessments. Mean PCL-5 reductions were 1.1, 12.4 and 14.6 points in Arms A, B and C (both intervention arms p